Kansas plays - Killian, Chloris (Kansas State University, 1983)
The Report of this project includes: 1) a summary of five years of study; 2) an appendix that will be composed of illustrations and copies of relevant theater programs, photographs and news releases. I have written nine plays in the five years of attending K-State classes. Five have received special treatment in the Speech Department. The plays which I am submitting as part of this report are those five, which are as follows: ONLY GOOD BUSINESS, produced in the Purple Masque Theatre in April 1981. THE DUST STORM WEDDING, produced in the Purple Masque Theatre in October 1981, entered in the January 1982 ACTF contest. MR. STRATHAN IS DYING, received a special reading in December, 1979 by the Writers' Stage of the Department of Speech. TOO MUCH PRIDE, a one act play, was read at the Senior Center in Manhattan and in the Holidome at a Kansas State Seminar in April, 1983.
Keywords: Kansas--Drama